(untitled) - Ferreira, Sonia Maria Barbosa; Pinheiro, Vandira Maria dos Santos; Sá, Eva Mila Miranda; Alvarenga, Gabriel Carvalho (Brazilian Journal of Sexually Transmitted Diseases, 1998)
This article analyzes some varia bles related to the use of condom by adolescents of Staces schools and State highschools. placed in the city district of Caramujo in Niterói, RJ. A quanti-qualitative research was accomplished with a aleatory proporcional sample that corresponded to 41.5% (125 people answered) of che scudencs of the age group from 15 to 19 years of the morning and night shifts of the State School Luciano Pestre (CELP). Thc insrrumenc used for the coUection of data was a questionnaire with 34 subjects of a wider research of Professor Vandira Maria dos Santos Pinheiro, Educacion in Health: the risk subject and prevention of the Sexually Transmined Diseases in adolescence. lt has becn opted for the analyzes of 5 subject.s studied in this anicle for referring more directly to the use of condom. The students of both sexes answered individually to the questionnaire in the class rooms. undergoing the authors of the article coordinacion in the period of May and June of 1996. The result of the analyzes showed chac adolcscencs began their sexual activityprecociously: the prioricized sexual relacionships were held with just one parmer and, as a second option, with jusc one and casual parmers’ simulcaneity in both sexes. The condom is used by most of the boys. The srudied adolescems presem fraccional and superficial knowledge on sexuality and STD/HIV / ALDS. These and other subjects which were parr in a wider scudy need to be more worked out cogether by the members of the education and of health reams who have an active panicipation ar CELP and in rhe nearestcommuniries (local health clinics, parents and ciry districts’ associations).